Host Country Restrictions, Choice of Entry Mode and Japanese Subsidiaries Performance in Developing Countries - Mohamad, Norhidayah; Hoshino, Yasuo (2013)
This paper empirically examines the effects of a host government’s local ownership restrictions, the choice of entry mode and Japanese subsidiaries performance in two selected developing countries namely Malaysia and Thailand that received among the highest Japanese FDI for fiscal years 2003 through 2009. The purpose of this paper is to investigate the influence of host government restriction by using subsidiary’s financial data as the performance indicator from ORBIS database. Our sample consists of 1267 cases. The results reveal that local host government restriction significantly influence the choice of entry mode and subsidiaries performance in the two developing countries.